2020
DOI: 10.1016/j.molcel.2020.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The Short- and Long-Range RNA-RNA Interactome of SARS-CoV-2

Abstract: Highlights d Comprehensive RNA-RNA networks of the SARS-CoV-2 genome and subgenomes inside cells d Long-range structures spanning thousands of bases resulting in dynamic topologies d Multiple site-specific interactions between host and virus RNAs d An arch around the ribosomal frameshifting element is under purifying selection

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
193
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 187 publications
(215 citation statements)
references
References 68 publications
21
193
1
Order By: Relevance
“…A highly conserved structure element, stemming from the multi-branched loop of the HVR, is the stem-loop II-like motif (s2m). This stem-loop shows extreme sequence and structure similarity to the second stem-loop from the 3 0 UTR of astroviruses and equine rhinovirus [70], and its existence in SARS-CoV-2 is supported under both in vitro and in vivo conditions by multiple studies [33,[35][36][37][38][39]. X-ray crystallography of the s2m revealed that the tertiary folding of the apical pentanucleotide GAGUA loop resembles that of a typical GNRA tetraloop, with the U bulging out of the stack [71].…”
Section: Utr Structuresmentioning
confidence: 92%
See 4 more Smart Citations
“…A highly conserved structure element, stemming from the multi-branched loop of the HVR, is the stem-loop II-like motif (s2m). This stem-loop shows extreme sequence and structure similarity to the second stem-loop from the 3 0 UTR of astroviruses and equine rhinovirus [70], and its existence in SARS-CoV-2 is supported under both in vitro and in vivo conditions by multiple studies [33,[35][36][37][38][39]. X-ray crystallography of the s2m revealed that the tertiary folding of the apical pentanucleotide GAGUA loop resembles that of a typical GNRA tetraloop, with the U bulging out of the stack [71].…”
Section: Utr Structuresmentioning
confidence: 92%
“…A first consensus model of the 5 0 UTR was originally proposed by comparative analysis of nine CoV from the three major CoV groups (alpha, beta, and gamma-CoV), and identified the three major conserved stem-loops SL1, SL2, and SL4 [32]. All three SLs have been consistently predicted and experimentally verified in SARS-CoV-2 [33][34][35][36][37][38][39]. Besides these, up to eight SLs can be present in CoV 5 0 UTRs, with some degree of variation across different genera ( Figure 1).…”
Section: Utr Structuresmentioning
confidence: 99%
See 3 more Smart Citations